One-Dimension Finite Element Modeling of Grouted Ground Anchor - Al-Baghdadi, N. H.; Ahmed, B. A.; Al-Jorany, A. N. (Engineering, Technology & Applied Science Research, 2022)
In the present research work, a one-dimension finite element model has been developed to simulate both compression and tension types of grouted ground anchors. The steel tendon-grout interface has been modeled by using the local bond-slip model, while the soil-grout interface has been modeled with a series of perfectly elastic plastic springs. The verification of the proposed one-dimension finite element model has been made by comparison of the model results with a three-dimension finite element model developed by commercial finite element software PLAXIS, and with the results of field tests of tension-type grouted ground anchor. A parametric study has been made to study the load-transfer mechanism for both types of anchors, compression, and tension. The compression-type anchor exhibits less displacement than the tension one under the same applied load. The developed strain in the grouted body of the compression-type anchor is much smaller than the tension-type one, regardless of the type of strain.